Prosopon Rhomaikon : Ergänzende Studien zur Prosopographie der mittelbyzantinischen Zeit - Beihammer, Alexander Daniel; Krönung, Bettina; Ludwig, Claudia (2017)
This volume includes 17 studies that present aspects of the Prosopography of the Middle Byzantine Period. The book`s thematic focus is on structural developments, major personalities, and the Byzantine Empire`s relations with the West.